On the Impact of Climate Change Policies on the Clean Technology Innovation: Evidence from Patent Data Analysis - Balcilar Mehmet; Agan Busra (Environmental and Climate Technologies, 2023)
This study investigates the role of environmental policies and regulations in mitigating climate change by promoting clean innovations and discouraging dirty ones. Utilizing nonparametric copula and quantile estimation techniques, along with carefully constructed innovation variables based on patents from 2000 to 2021 across 34 countries, the research examines the effects of policy interventions and external events on energy-related innovations. Findings reveal that climate policy interventions effectively promote clean innovation, particularly at higher levels, and discourage dirty innovations. Therefore, climate change policies and regulations are crucial in achieving net-zero carbon emission targets.